EMANCIPATION THROUGH ART IN JACQUES RANCIÈRE - das Chagas , José Soares (Seven Editora, 2024)
This article has as its scope the question of emancipation through art from the philosophy of Jacques Rancière. In his work The Ignorant Master, emancipation is seen as an affirmation of the equality of intelligences that occurs from the beginning of the formative process as opposed to the explanatory order in which there is a need for the submission of the intelligence of the apprentices to the master, who attests to their cognitive superiority through explanations. To address this problem, we developed the theme in three moments. In the first part, we discussed what an aesthetic education would be based on the definition of education and art. In the second, we approach the concept of emancipation as the starting point of a practice in which the teacher is an agent who organizes the teaching-learning process, but does not dominate intelligence because it presupposes an equality of cognitive capacity. In the last part, we dealt with what this emancipatory practice of the student would be within the universe of art. In this sense, learning and artistic practice are understood as paths of autonomy and freedom by leading the human being to the recognition of the equal capacity to feel, understand and express the poetry of the world. DOI:https://doi.org/10.56238/sevened2024.037-013